The Semiotic Model as Intertextual Interpretation of «Sign Decoding» in the Work of Art - Хайруліна, Наіля Фаритівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article under consideration is devoted to the use of semiotic modeling in the analysis of literary works. Based on the outstanding works in semiotics by Yriy Loman, the article revealed the «evolution» of the term «literary model», its necessity in the process of  work’s interpretation and gives a classification of possible types of literary models. The accentuation on the semiotics and cultural modeling study is caused by a widespread popularity in modern literary criticism. It is proved that semiotic model consists of constant and  transient components. While the constants implied decimal analysis of  time, psychological and symbolic spaces in the art work, the transitionals enter the extrapolation of perception of objective reality and, therefore, not always could be studied in the works. The given algorithm of practical detection of components the semiotic model «Life is a Fair» based on the works of Ukrainian and English literature proves that semiotic modeling is the subject of a thorough theoretical and literary study nowdays.